Quality of students life and its role in strengthening the social responsibility with the students of Adrar University - Bouchra Bakhtaoui; Cheikh Saous (مجلة الاجتهاد للدراسات القانونية والاقتصادية)
The current study aims at determining the quality of student life in the University of Adrar and its role in strengthening the social responsibility. The study is based on the descriptive analytical method and applied on a sample composed of 90 students randomly chosen, however for the processing, the R program, pack SEMinR were applied.